When the giants sneeze a study on the International Monetary Policy spillovers in the Philippines - Endaya, Mark Joseph V.; Mantuano, Jordan Jae C.; Pajaron, Marjorie C. (Quezon City School of Economics, University of the Philippines Diliman, 2023)
In an increasingly interconnected global economy shaped by globalization, smaller economies like the Philippines face heightened vulnerability to the monetary policy decisions of larger economies. This paper aims to investigate the varying magnitude and dynamics of international monetary spillovers on the Philippines’ policy rate and whether there has been a structural change in the transmission process of spillovers in the Philippines before and after the 2008 global financial crisis. Our primary focus is on the United States (US), Japan, and the People's Republic of China (PRC) because of their status as the Philippines' largest trading partners. Using OLS, Vector Autoregression (VAR), and Structural VAR (SVAR), our findings uncover distinct patterns in spillover effects. US policy rate shocks have a significant short-term impact on the Philippine policy rate, while Japanese policy rate fluctuations shape the Philippine policy rate over the long term. However, PRC policy rate shocks do not significantly influence the Philippine policy rate. Nonetheless, we find that only monetary shocks from PRC, through its policy rates, significantly affect Philippine exchange rates. We also identify a structural shift in spillover transmission following the 2008 global financial crisis from the US and Japan. By providing comprehensive insights into the differential effects of international monetary shocks, our research can equip policymakers with valuable information to better understand and manage spillovers, hopefully helping them to formulate more effective monetary policies and promote economic stability in an interconnected global financial landscape.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Monetary policy -- Effect of foreign exchange rates on -- Philippines; Monetary policy -- Effect of foreign exchange rates on -- Econometric models. -- Philippines